Empirical Analysis of Information Security Awareness in the Business and Public Sectors of Hungary - Andras Nemeslaki; Peter Sasvari (Central and Eastern European eDem and eGov Days 2015. Time for a European Internet?, 2015)
Based on an empirical study of 300 employees in the public and business sectors of Hungary we found that the level of information security awareness can be considered good at corporations in the business sector, and at public institutions and state-owned organizations in the public sector. Employees need further training in this area mainly at medium-sized enterprises (employing less than 250 people), at for-profit local government organizations and at nearly a quarter of the local governments. Due to the low level of information security awareness, some parts of the micro and small-sized enterprises are in need of immediate changes in terms of organizational operations. The deficient knowledge of employees about information security gives room for grave concern at several local government organizations. Our sample also indicated that people with higher level of digital literacy show a higher level of information security awareness both in the business and the public sector.
Keywords: M15; M10; 330; Hungary; Business sector; Public sector; Information Security Awareness